Composite purification process for preparing high-purity microcrystalline graphite in large quantities with low energy consumption

CN122940165APending Publication Date: 2026-10-20HENAN ZHULINSAXIN CARBON CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610717732.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-22
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]针对现有技术的不足,本发明提供了低能耗大批量制备高纯微晶石墨的复合提纯工艺,解决了传统微晶石墨提纯工艺能耗高,且在除杂过程中可溶性硅酸极易发生脱水缩聚生成网状硅酸凝胶,导致过滤设备堵塞,同时前期解离析出的铁等金属杂质易在洗涤阶段发生水解沉淀并重新附着于石墨层间,造成提纯纯度下降以及连续生产困难的问题

Benefits of technology

1、本发明通过采用氢氧化钠、氢氧化钾与去离子水组成的低共熔亚熔盐体系进行解离反应,利用混合碱形成的低熔点特性以及固相溶解产生的水化热,降低了升温过程所需的外部加热能耗;同时,体系中钾离子的引入增强了对微晶石墨层间硅酸盐杂质的穿透与解离能力,提高了矿相杂质的脱除深度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to the field of non-metallic mineral purification technology, and discloses a composite purification process for the large-scale preparation of high-purity microcrystalline graphite with low energy consumption. The process includes mixing microcrystalline graphite raw powder with a eutectic submolten salt system containing sodium hydroxide, potassium hydroxide, and deionized water, and carrying out a dissociation reaction under pressure and heating. After cooling and depressurization, an ammonium sulfate aqueous solution is added to the system for further reaction, controlling the final pH value to 11.6-12.0. Solid-liquid separation yields a wet filter cake containing some residual ammonia and a slightly alkaline mother liquor. The residual alkali components carried in the pores of the wet filter cake neutralize some of the free acid in the acid leaching slurry. By controlling the solid-liquid ratio of the wet filter cake to the composite acid leaching base liquor, the pH value of the acid leaching slurry gradually increases and eventually reaches a slightly acidic range of 2.71-2.81. Finally, the product is obtained after solid-liquid separation, washing, and drying. This invention utilizes the eutectic effect to reduce dissociation energy consumption, leverages a natural buffer system to spontaneously regulate pH and synergistically complex and remove impurities, prevents secondary precipitation of impurities, and reduces acid and alkali consumption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of non-metallic mineral purification technology, specifically a composite purification process for the large-scale preparation of high-purity microcrystalline graphite with low energy consumption. Background Technology

[0002] Microcrystalline graphite possesses excellent physicochemical stability, electrical conductivity, and high-temperature resistance, making it widely used in metallurgy, chemical engineering, and new energy industries. Naturally mined microcrystalline graphite ore typically contains significant amounts of associated mineral impurities such as silicates, iron, and aluminum, requiring purification to meet the high-purity demands of advanced industrial applications. Currently, chemical purification methods, particularly the alkali-acid method, are commonly used in industry to remove impurities from microcrystalline graphite. The conventional process involves first reacting the silicon-containing impurities in the graphite ore with a high-temperature, strong alkali to generate soluble silicates. After filtration, acid leaching converts the metallic impurities into a soluble salt solution, followed by washing and drying to obtain the final product.

[0003] In actual large-scale continuous production, existing conventional processes have certain limitations. Traditional alkali fusion reactions often use a single alkaline system, requiring high melting activation temperatures, placing high demands on the resilience of reaction equipment, and consuming a large amount of external heating energy. During the subsequent acid leaching process to remove impurities, the silicates entering the system are converted into free soluble silicic acid in an acidic environment. As the reaction proceeds, silicic acid molecules readily undergo spontaneous dehydration and condensation reactions, generating silicic acid gels with a network structure. This gel reduces the fluidity and dehydration properties of the slurry, leading to increased pressure filtration resistance in the subsequent solid-liquid separation stage, easily causing filter pore blockage in the filtration equipment, and affecting production turnover efficiency. At the same time, iron, aluminum, and other metal impurity ions dissolved in the liquid phase during the acid leaching stage are prone to hydrolysis reactions and the formation of metal hydroxide precipitates during the later pure water washing step, as the free acid is washed away and the local pH value of the system increases. These newly formed precipitates will re-adhere to the surface of graphite particles or enter the graphite interlayer, and conventional water washing is insufficient to completely remove them, ultimately leading to a decrease in the purity of the extracted microcrystalline graphite product. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a composite purification process for the large-scale preparation of high-purity microcrystalline graphite with low energy consumption. This process solves the problems of high energy consumption in traditional microcrystalline graphite purification processes, the easy dehydration and condensation of soluble silica to form a network silica gel during the impurity removal process, which leads to clogging of the filtration equipment, and the tendency of metal impurities such as iron that are dissociated and precipitated in the early stage to hydrolyze and precipitate during the washing stage and re-attach to the graphite layers, resulting in a decrease in purification purity and difficulties in continuous production.

[0005] To address the above problems, the present invention provides the following technical solution: In a first aspect, the present invention provides a composite purification process for the low-energy-consumption, high-volume preparation of high-purity microcrystalline graphite, employing the following technical solution: A composite purification process for the low-energy, high-volume preparation of high-purity microcrystalline graphite includes the following steps: Microcrystalline graphite ore powder was mixed with a eutectic submolten salt system containing sodium hydroxide, potassium hydroxide and deionized water, and a dissociation reaction was carried out under pressure and heating conditions to obtain the reaction system. The reaction system was cooled and depressurized, and an ammonium sulfate aqueous solution was added to react and obtain an alkaline precipitate slurry. The amount of ammonium sulfate aqueous solution added was controlled until the final pH value of the alkaline precipitate slurry reached 11.6-12.0. Subsequently, the alkaline precipitate slurry was subjected to solid-liquid separation to obtain a wet filter cake containing some residual ammonia and a slightly alkaline mother liquor. The alkaline wet filter cake containing the ammonia and ammonium salt buffer system was added to a composite acid leaching base solution containing hydrochloric acid base solution, sodium lignosulfonate, and tetrasodium ethylenediaminetetraacetate for acid leaching. The leaching reaction yields an acid-leaching slurry. Under mechanical stirring, the residual alkali carried in the pores of the wet filter cake neutralizes some of the free acid in the acid-leaching slurry. By controlling the solid-liquid ratio of the wet filter cake and the composite acid-leaching base liquid, the pH value of the acid-leaching slurry gradually increases and eventually reaches a slightly acidic range of 2.71-2.81, resulting in an acid-leached slurry. The acid-leached slurry undergoes solid-liquid separation to obtain a final filter cake. The final filter cake is washed and dried to obtain a high-purity microcrystalline graphite product.

[0006] By adopting the above technical solution, this process can effectively reduce energy consumption, decrease acid and alkali consumption, and improve product purity. Its core innovative mechanism lies in the coherent system design from dissociation to acid leaching: When microcrystalline graphite ore powder is mixed with sodium hydroxide and potassium hydroxide, the melting point of the entire mixture decreases due to the eutectic effect of these two strong alkalis. With a very small amount of deionized water, a sub-molten salt medium can be formed under pressure and heating. This medium not only has a high boiling point, but also exhibits extremely active hydroxide ions, which readily penetrate into the microcrystalline graphite particles. Thus, under conditions far lower than conventional high-temperature alkali fusion, the skeleton of gangue impurities such as quartz and aluminosilicates can be depolymerized and transformed into soluble silicates and aluminates, reducing heat consumption at the source.

[0007] After dissociation and cooling / depressurization, an excess of free alkali is inevitable. Direct acid washing would consume a massive amount of acid. Therefore, this process introduces an ammonium sulfate aqueous solution for neutralization. Ammonium sulfate not only consumes excess alkali to generate readily soluble sulfates but also releases ammonia. Maintaining the final pH between 11.6 and 12.0 is a crucial equilibrium point. In this slightly alkaline environment, the previously generated silicates and aluminates maintain good water solubility, preventing the precipitation of silicate polymer colloids due to a sudden pH drop, which could contaminate the graphite particles. After solid-liquid separation, the resulting wet filter cake retains newly generated ammonia and a small amount of unreacted ammonium sulfate within its internal pores, leaving a suitable amount of slightly alkaline residual liquid in the pores of the solid material.

[0008] After the wet filter cake with a buffer system is added to the composite acid leaching solution, the hydrochloric acid preferentially dissolves the metallic impurities. The buffer component in the filter cake undergoes a neutralization reaction with the hydrochloric acid, consuming hydrogen ions and causing the pH value of the system to rise slowly to 2.71-2.81 without external addition. This spontaneous process avoids local pH fluctuations. During this process, sodium lignosulfonate prevents carbon particle agglomeration through steric hindrance; simultaneously, the free ethylenediaminetetraacetic acid particles initially precipitated in the strong acid redissolve as the pH rises and regain their complexing activity, forming stable water-soluble complexes with iron, calcium, and other ions, thereby preventing the metallic impurities from forming hydroxide precipitates and being re-adsorbed during subsequent washing.

[0009] Finally, the slurry that has been thoroughly acid-leached and has completed the complexation of impurities is directly subjected to solid-liquid separation and pure water washing. This allows the impurities encapsulated in the liquid phase to be carried away with the mother liquor, easily obtaining high-purity microcrystalline graphite.

[0010] Preferably, the eutectic submolten salt system is made from the following raw materials in parts by weight: 40-58 parts sodium hydroxide, 42-60 parts potassium hydroxide, and 15-21 parts deionized water. By adopting the above technical solution and locking the mass ratio of the two alkalis within this range, the optimal eutectic state is activated, ensuring that the system has good liquid flowability at the set temperature. The control of deionized water is also crucial; 15 to 21 parts are just enough to start the initial alkaline depolymerization. Too much water will dilute the effective ion concentration and slow down the depolymerization rate, while too little water will make the slurry too viscous and thus hinder the mass transfer process.

[0011] Preferably, the preparation method of the eutectic submolten salt system includes: uniformly mixing the sodium hydroxide and potassium hydroxide to obtain a dry mixed alkali; slowly adding deionized water to the dry mixed alkali; utilizing the heat of hydration and heating to 90-120°C; and stirring in a sealed environment until a completely molten, homogeneous liquid state is obtained, thus obtaining the eutectic submolten salt system. By adopting the above technical solution, this operation utilizes the large amount of heat of hydration released when the solid alkali comes into contact with water. Using this as an initial heat source, combined with external supplementary heating at 90-120°C, the solid mixed alkali can be quickly converted into a homogeneous submolten salt liquid phase. This not only distributes the energy consumption pressure of external heating, but the continuous stirring in a sealed state also cuts off the path of water evaporation and loss at high temperatures.

[0012] Preferably, the composite acid leaching base solution is made from the following raw materials in parts by weight: 990-996 parts of the hydrochloric acid base solution with an initial pH value of 0.3-0.7, 1-3 parts of the sodium lignosulfonate, and 3-7 parts of the tetrasodium ethylenediaminetetraacetate. By adopting the above technical solution and using a near-limit strong acid base solution, sufficient hydrogen ions are reserved to flush out buffer salts brought in by the filter cake and dissolve residual mineral impurities. The specific ratio of sodium lignosulfonate to tetrasodium ethylenediaminetetraacetate is calculated based on the general specific surface area of ​​microcrystalline graphite and the abundance of commonly associated metallic impurities. A ratio that is too high will increase the subsequent treatment cost of the waste liquid, while a ratio that is too low will fail to suppress secondary precipitation of impurities.

[0013] Preferably, the preparation method of the composite acid leaching base solution includes: slowly adding sodium lignosulfonate and tetrasodium ethylenediaminetetraacetate sequentially to the hydrochloric acid base solution, and continuously mechanically stirring at 20-30°C, so that the tetrasodium ethylenediaminetetraacetate is converted into free ethylenediaminetetraacetic acid particles under strong acid conditions and uniformly dispersed, thereby obtaining the composite acid leaching base solution, which is a uniformly dispersed suspension. By adopting the above technical solution, once the tetrasodium ethylenediaminetetraacetate encounters the hydrochloric acid base solution with an extremely low pH value, it will undergo protonation, and its solubility will drop sharply, thus precipitating out. At this time, with the assistance of sodium lignosulfonate for dispersion and mechanical agitation, these solid particles will not agglomerate, but will form a suspension. The function of this special pre-dispersion form is that when the pH value of the slurry slowly rises due to the subsequent addition of filter cake, the complexing agent particles can dissolve simultaneously in all corners of the system and release their capturing ability, avoiding the leakage of impurities caused by local concentration differences.

[0014] Preferably, the mass ratio of the microcrystalline graphite ore powder to the eutectic submolten salt system is 100:(115-121). By adopting the above technical solution, this solid-liquid ratio is the critical point for balancing reaction efficiency and material cost. It allows the submolten salt to completely coat each particle of ore powder, providing sufficient reaction contact surface, while also controlling the total amount of alkali added, preventing unnecessary increase in material load to neutralize these excess free alkalis.

[0015] Preferably, the target temperature for the dissociation reaction is 220-280℃, the pressure is controlled to be stable at 1.5-3.5 MPa, and the reaction time is 1.5-2.5 hours. By adopting the above technical solution, due to the vapor pressure characteristics of the submolten salt system, under a pressure of 1.5 to 3.5 MPa, the trace amounts of water in the system are forcibly retained in the liquid phase and cannot boil away, thus maintaining the stability of the entire reaction medium. Under such physical conditions, a temperature of 220 to 280℃ combined with a constant temperature of one and a half to two and a half hours is just enough to completely break down the dense crystalline framework of the gangue minerals.

[0016] Preferably, cooling and depressurizing the reaction system means cooling the reaction system to 50°C and depressurizing it to atmospheric pressure; the mass fraction of the ammonium sulfate aqueous solution added to the reaction system is 15.0%. By adopting the above technical solution, cooling to 50°C and depressurizing is purely for process safety and material loss considerations. If the aqueous solution is added directly without cooling, the high temperature can easily cause violent boiling and splashing of the slurry, and the generated ammonia gas will also evaporate and dissipate in large quantities instantly. The 15.0% ammonium sulfate concentration balances effective replenishment of reactants and slurry volume control; any more water would bring additional drainage pressure to the subsequent solid-liquid separation.

[0017] Preferably, during the acid leaching reaction, the pH value of the acid leaching slurry spontaneously and slowly increases from an initial 0.3-0.7; the entire acid leaching reaction is carried out continuously for 1.5 hours at 20-30°C. By adopting the above technical solution, maintaining a room temperature range of 20-30°C not only saves heating energy consumption but also suppresses the large-scale volatilization of acid mist. The 1.5-hour travel time naturally matches the inherent kinetic rhythm of the buffer system's consumption of hydrogen ions and the complexation reaction itself. This gentle pH rise and mass transfer environment are conducive to the more thorough dissolution and complexation of all deeply released impurity metals.

[0018] Preferably, when performing solid-liquid separation on the acid-leached slurry, a filter press is used for filtration, with an operating pressure of 0.6 MPa. Washing the final filter cake involves using deionized water to wash the final filter cake until the washing filtrate is neutral. By adopting the above technical solution, the filtration pressure of 0.6 MPa is sufficient to penetrate the dense filter cake layer formed by the stacked fine graphite particles, forcibly expelling the mother liquor filled with impurities and complexes. The subsequent deionized water washing operation also utilizes this mechanical pressure to forcefully flush away trace amounts of residual salt deep within the micropores, continuing until the filtrate is neutral. This is a crucial washing step to ensure the purity of the final microcrystalline graphite product meets the standards.

[0019] This invention provides a composite purification process for the low-energy, high-volume preparation of high-purity microcrystalline graphite. It offers the following advantages: 1. This invention uses a eutectic submolten salt system composed of sodium hydroxide, potassium hydroxide and deionized water to carry out the dissociation reaction. It utilizes the low melting point characteristics of the mixed alkali and the heat of hydration generated by solid phase dissolution to reduce the external heating energy consumption required for the heating process. At the same time, the introduction of potassium ions in the system enhances the penetration and dissociation ability of silicate impurities in the interlayer of microcrystalline graphite, and improves the removal depth of mineral phase impurities.

[0020] 2. This invention utilizes an alkaline wet filter cake with an ammonia and ammonium salt buffer system mixed with a composite acid leaching base liquor containing sodium lignosulfonate. This causes the pH value of the acid leaching system to gradually rise from strongly acidic and stabilize at a weakly acidic level. During this process, sodium lignosulfonate adsorbs onto the surface of monomeric silicic acid due to steric hindrance, blocking the path of silicic acid molecules dehydrating and condensing into a network gel. This maintains the good dehydration properties of the slurry, reduces pressure filtration resistance, and shortens the solid-liquid separation time.

[0021] 3. This invention introduces tetrasodium ethylenediaminetetraacetate into the composite acid leaching solution, enabling simultaneous slow release during the dynamic pH changes of the acid leaching reaction. In the initial stage of the reaction, the high concentration of hydrogen ions in the system fully dissolves metal oxide impurities. When the pH of the system rises and stabilizes in the weakly acidic range, tetrasodium ethylenediaminetetraacetate forms a stable soluble complex with the free metal ions, preventing the metal impurities from hydrolyzing and precipitating in the subsequent water washing stage and re-attaching to the graphite interlayer, thus ensuring the final purity of the microcrystalline graphite product. Attached Figure Description

[0022] Figure 1 This is a graph showing the measured pH value of the acid leaching slurry as a function of reaction time in an embodiment of the present invention. Figure 2 This is a bar chart showing the monomer silicate concentration of the acid leaching slurry at different measured pH values ​​in the embodiments of the present invention; Figure 3 The bar chart shows the iron content and average filtration time of the final products of the embodiments of the present invention and the comparative examples (where (a) is a comparison of iron content and (b) is a comparison of average filtration time). Detailed Implementation

[0023] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] Preparation Examples 1-6: Preparation Example 1: This preparation example provides a method for preparing a eutectic submolten salt system, including the following steps: 49 kg of sodium hydroxide and 51 kg of potassium hydroxide were added to a mixing device with a heating jacket and mixed evenly to obtain a dry mixed alkali. 18 kg of deionized water was slowly added to the dry mixed alkali, and the mixture was heated to 90 to 120°C using the heat of hydration and stirred in a sealed manner until it reached a completely melted homogeneous liquid state, thus obtaining a eutectic submolten salt system.

[0025] Preparation Example 2: This preparation example provides a method for preparing a eutectic submolten salt system, including the following steps: 40 kg of sodium hydroxide and 60 kg of potassium hydroxide were added to a mixing device with a heating jacket and mixed evenly to obtain a dry mixed alkali. 15 kg of deionized water was slowly added to the dry mixed alkali and heated to 90 to 120°C using the heat of hydration. The mixture was stirred in a sealed container until it reached a completely melted, homogeneous liquid state, thus obtaining a eutectic submolten salt system.

[0026] Preparation Example 3: This preparation example provides a method for preparing a eutectic submolten salt system, including the following steps: 58 kg of sodium hydroxide and 42 kg of potassium hydroxide were added to a mixing device with a heating jacket and mixed evenly to obtain a dry mixed alkali. 21 kg of deionized water was slowly added to the dry mixed alkali and heated to 90 to 120°C using the heat of hydration. The mixture was stirred in a sealed container until it reached a completely melted, homogeneous liquid state, thus obtaining a eutectic submolten salt system.

[0027] Preparation Example 4: This preparation example provides a method for preparing a composite acid leaching base solution, including the following steps: 993 kg of hydrochloric acid base solution with an initial pH of 0.5 was added to a mixing reactor with a polytetrafluoroethylene liner. Then, 2 kg of sodium lignosulfonate and 5 kg of tetrasodium ethylenediaminetetraacetate were added slowly in sequence. The mixture was continuously mechanically stirred at 20-30°C to convert the tetrasodium ethylenediaminetetraacetate into free ethylenediaminetetraacetic acid particles under strong acid conditions and to disperse them uniformly, thus obtaining a uniformly dispersed suspension-like composite acid leaching base solution.

[0028] Preparation Example 5: This preparation example provides a method for preparing a composite acid leaching base solution, including the following steps: 996 kg of hydrochloric acid base solution with an initial pH of 0.7 was added to a mixing reactor with a polytetrafluoroethylene liner. Then, 1 kg of sodium lignosulfonate and 3 kg of tetrasodium ethylenediaminetetraacetate were added slowly in sequence. The mixture was continuously mechanically stirred at 20-30°C to convert the tetrasodium ethylenediaminetetraacetate into free ethylenediaminetetraacetic acid particles under strong acid conditions and to disperse them uniformly, thus obtaining a uniformly dispersed suspension-like composite acid leaching base solution.

[0029] Preparation Example 6: This preparation example provides a method for preparing a composite acid leaching base solution, including the following steps: 990 kg of hydrochloric acid base solution with an initial pH of 0.3 was added to a mixing reactor with a polytetrafluoroethylene liner. Then, 3 kg of sodium lignosulfonate and 7 kg of tetrasodium ethylenediaminetetraacetate were added slowly in sequence. The mixture was continuously mechanically stirred at 20-30°C to convert the tetrasodium ethylenediaminetetraacetate into free ethylenediaminetetraacetic acid particles under strong acid conditions and to disperse them uniformly, thus obtaining a uniformly dispersed suspension-like composite acid leaching base solution.

[0030] Examples 1-5: Example 1: This embodiment provides a composite purification process for the low-energy, large-scale preparation of high-purity microcrystalline graphite. This embodiment is based on pilot-scale large-scale preparation and includes the following steps: Step 1, submolten salt dissociation: 100 kg of microcrystalline graphite raw ore powder and 118 kg of the eutectic submolten salt system prepared by Preparation Example 1 were put into a 3.0 MPa jacketed pressure reactor, sealed and heated to 250°C, and the pressure inside the reactor was controlled to be stable at 2.5 MPa. Mechanical stirring was turned on and the reaction was continued for 2 hours.

[0031] The second step, salting out and buffer setting: After the reaction is completed, the pressurized reactor system is cooled to 50°C and depressurized to atmospheric pressure. A 15.0% ammonium sulfate aqueous solution is slowly and continuously pumped into the reactor. The pH of the system is monitored in real time, and the amount added is controlled until the pH of the alkali precipitation slurry reaches 11.8. This allows some of the ammonia generated in the system to remain in the system to form a buffer solution. The alkali precipitation slurry is then pumped into a horizontal centrifuge and a diaphragm filter press for solid-liquid separation. A wet filter cake containing some residual ammonia and slightly alkaline mother liquor is collected.

[0032] The third step, acid leaching and spontaneous complexation: All the alkaline wet filter cake collected above was transferred and added to an acid-resistant reactor with a polytetrafluoroethylene liner containing 1000 kg of the composite acid leaching base solution prepared in Preparation Example 4. Under the conditions of 20-30°C and continuous mechanical stirring, the pH value of the acid leaching slurry was spontaneously and slowly changed from the initial 0.5 to a stable weakly acidic range of 2.71-2.81 by the buffer system introduced by the alkaline wet filter cake. The entire acid leaching reaction process lasted for 1.5 hours.

[0033] The fourth step is washing and drying: the slurry after acid leaching is pumped into a filter press for filtration and separation. The operating pressure is set to 0.6 MPa, and the average filtration time is measured to be 16.4 min / m3. The final filter cake is washed with deionized water until the washing filtrate is neutral. Finally, the final filter cake is collected and dried to obtain high-purity microcrystalline graphite product.

[0034] Example 2: This embodiment provides a composite purification process for the low-energy, high-volume preparation of high-purity microcrystalline graphite, including the following steps: Step 1, submolten salt dissociation: 100 kg of microcrystalline graphite ore powder and 115 kg of the eutectic submolten salt system prepared by Preparation Example 2 were put into a 2.0 MPa jacketed pressure reactor, sealed and heated to 220 °C, and the pressure inside the reactor was controlled to be stable at 1.5 MPa. Mechanical stirring was turned on and the reaction was continued for 2.5 hours.

[0035] The second step, salting out and buffer setting: After the reaction is completed, the pressurized reactor system is cooled to 50°C and depressurized to atmospheric pressure. A 15.0% ammonium sulfate aqueous solution is slowly and continuously pumped into the reactor. The pH of the system is monitored in real time, and the amount added is controlled until the pH of the alkali precipitation slurry reaches 11.8. This allows some of the ammonia generated in the system to remain in the system to form a buffer solution. The alkali precipitation slurry is then pumped into a horizontal centrifuge and a diaphragm filter press for solid-liquid separation. A wet filter cake containing some residual ammonia and slightly alkaline mother liquor is collected.

[0036] The third step, acid leaching and spontaneous complexation: All the alkaline wet filter cake collected above was transferred and added to an acid-resistant reactor with a polytetrafluoroethylene liner containing 1000 kg of the composite acid leaching base solution prepared in Preparation Example 4. Under the conditions of 20-30°C and continuous mechanical stirring, the pH value of the acid leaching slurry was spontaneously and slowly changed from the initial 0.5 to a stable weakly acidic range of 2.71-2.81 by the buffer system introduced by the alkaline wet filter cake. The entire acid leaching reaction process lasted for 1.5 hours.

[0037] The fourth step is washing and drying: the slurry after acid leaching is pumped into a filter press for filtration and separation. The operating pressure is set to 0.6 MPa, and the average filtration time is measured to be 17.5 min / m3. The final filter cake is washed with deionized water until the washing filtrate is neutral. Finally, the final filter cake is collected and dried to obtain high-purity microcrystalline graphite product.

[0038] Example 3: This embodiment provides a low-energy-consumption, high-volume composite purification process for preparing high-purity microcrystalline graphite, including the following steps: Step 1, submolten salt dissociation: 100 kg of microcrystalline graphite ore powder and 121 kg of the eutectic submolten salt system prepared by Preparation Example 3 were put into a 4.0 MPa jacketed pressure reactor, sealed and heated to 280°C, and the pressure inside the reactor was controlled to be stable at 3.5 MPa. Mechanical stirring was turned on and the reaction was continued for 1.5 hours.

[0039] The second step, salting out and buffer setting: After the reaction is completed, the pressurized reactor system is cooled to 50°C and depressurized to atmospheric pressure. A 15.0% ammonium sulfate aqueous solution is slowly and continuously pumped into the reactor. The pH of the system is monitored in real time, and the amount added is controlled until the pH of the alkali precipitation slurry reaches 11.8. This allows some of the ammonia generated in the system to remain in the system to form a buffer solution. The alkali precipitation slurry is then pumped into a horizontal centrifuge and a diaphragm filter press for solid-liquid separation. A wet filter cake containing some residual ammonia and slightly alkaline mother liquor is collected.

[0040] The third step, acid leaching and spontaneous complexation: All the alkaline wet filter cake collected above was transferred and added to an acid-resistant reactor with a polytetrafluoroethylene liner containing 1000 kg of the composite acid leaching base solution prepared in Preparation Example 4. Under the conditions of 20-30°C and continuous mechanical stirring, the pH value of the acid leaching slurry was spontaneously and slowly changed from the initial 0.5 to a stable weakly acidic range of 2.71-2.81 by the buffer system introduced by the alkaline wet filter cake. The entire acid leaching reaction process lasted for 1.5 hours.

[0041] The fourth step is washing and drying: the slurry after acid leaching is pumped into a filter press for filtration and separation. The operating pressure is set to 0.6 MPa, and the average filtration time is measured to be 18.2 min / m3. The final filter cake is washed with deionized water until the washing filtrate is neutral. Finally, the final filter cake is collected and dried to obtain high-purity microcrystalline graphite product.

[0042] Example 4: This embodiment provides a low-energy-consumption, high-volume composite purification process for preparing high-purity microcrystalline graphite, including the following steps: Step 1, submolten salt dissociation: 100 kg of microcrystalline graphite raw ore powder and 118 kg of the eutectic submolten salt system prepared by Preparation Example 1 were put into a 3.0 MPa jacketed pressure reactor, sealed and heated to 250°C, and the pressure inside the reactor was controlled to be stable at 2.5 MPa. Mechanical stirring was turned on and the reaction was continued for 2 hours.

[0043] The second step, salting out and buffer setting: After the reaction is completed, the pressurized reactor system is cooled to 50°C and depressurized to atmospheric pressure. A 15.0% ammonium sulfate aqueous solution is slowly and continuously pumped into the reactor. The pH of the system is monitored in real time, and the amount added is controlled until the pH of the alkali precipitation slurry reaches 12.0. This allows some of the ammonia generated in the system to remain in the system to form a buffer solution. The alkali precipitation slurry is then pumped into a horizontal centrifuge and a diaphragm filter press for solid-liquid separation. A wet filter cake containing some residual ammonia and slightly alkaline mother liquor is collected.

[0044] The third step, acid leaching and spontaneous complexation: All the alkaline wet filter cake collected above was transferred and added to an acid-resistant reactor with a polytetrafluoroethylene liner containing 1000 kg of the composite acid leaching base solution prepared in Preparation Example 5. Under the conditions of 20-30°C and continuous mechanical stirring, the pH value of the acid leaching slurry was spontaneously and slowly changed from the initial 0.7 to a stable weakly acidic range of 2.71-2.81 by the buffer system introduced by the alkaline wet filter cake. The entire acid leaching reaction process lasted for 1.5 hours.

[0045] The fourth step is washing and drying: the slurry after acid leaching is pumped into a filter press for filtration and separation. The operating pressure is set to 0.6 MPa, and the average filtration time is measured to be 15.9 min / m3. The final filter cake is washed with deionized water until the washing filtrate is neutral. Finally, the final filter cake is collected and dried to obtain high-purity microcrystalline graphite product.

[0046] Example 5: This embodiment provides a low-energy-consumption, high-volume composite purification process for preparing high-purity microcrystalline graphite, including the following steps: Step 1, submolten salt dissociation: 100 kg of microcrystalline graphite raw ore powder and 118 kg of the eutectic submolten salt system prepared by Preparation Example 1 were put into a 3.0 MPa jacketed pressure reactor, sealed and heated to 250°C, and the pressure inside the reactor was controlled to be stable at 2.5 MPa. Mechanical stirring was turned on and the reaction was continued for 2 hours.

[0047] The second step, salting out and buffer setting: After the reaction is completed, the pressurized reactor system is cooled to 50°C and depressurized to atmospheric pressure. A 15.0% ammonium sulfate aqueous solution is slowly and continuously pumped into the reactor. The pH of the system is monitored in real time, and the amount added is controlled until the pH of the alkali precipitation slurry reaches 11.6, so that some of the ammonia water generated in the system is retained in the system to form a buffer solution. Then, the alkali precipitation slurry is pumped into a horizontal centrifuge and a diaphragm filter press for solid-liquid separation, and a wet filter cake containing some residual ammonia and slightly alkaline mother liquor is collected.

[0048] The third step, acid leaching and spontaneous complexation: All the alkaline wet filter cake collected above was transferred and added to an acid-resistant reactor with a polytetrafluoroethylene liner containing 1000 kg of the composite acid leaching base solution prepared in Preparation Example 6. Under the conditions of 20-30°C and continuous mechanical stirring, the pH value of the acid leaching slurry was spontaneously and slowly changed from the initial 0.3 by the buffer system brought in by the alkaline wet filter cake, and finally stabilized in the weakly acidic range of 2.71-2.81. The entire acid leaching reaction process lasted for 1.5 hours.

[0049] The fourth step is washing and drying: the slurry after acid leaching is pumped into a filter press for filtration and separation. The operating pressure is set to 0.6 MPa, and the average filtration time is measured to be 16.8 min / m3. The final filter cake is washed with deionized water until the washing filtrate is neutral. Finally, the final filter cake is collected and dried to obtain high-purity microcrystalline graphite product.

[0050] Comparative Examples 1-5: Comparative Example 1: Compared to Example 1, the difference lies in the use of a traditional high-temperature soda ash roasting and pure acid leaching process. Specifically, the first step does not use a eutectic submolten salt system, but instead uses only pure sodium hydroxide for dry roasting at a temperature as high as 600°C; the second step eliminates the salting-out and buffer pre-setting operations, replacing them with direct quenching of the roasted material with pure water until neutral; the third step does not use a composite acid leaching base solution, but directly uses strong hydrochloric acid for leaching (maintaining the system pH < 1 throughout the leaching process), and no sodium lignosulfonate or tetrasodium ethylenediaminetetraacetate is added throughout the process. All other steps remain the same.

[0051] Comparative Example 2: Compared with Example 1, the difference is that in the first step of submolten salt dissociation, instead of using a eutectic submolten salt system composed of sodium hydroxide and potassium hydroxide, a single-alkali submolten salt system prepared by 100 kg of pure sodium hydroxide and 18 kg of deionized water is used (the reaction temperature and pressure are still maintained at 250°C and 2.5 MPa), while the rest are the same.

[0052] Comparative Example 3: Compared to Example 1, the differences are as follows: After the second step of submolten salt dissociation, instead of adding ammonium sulfate aqueous solution to the cooled system for salting out and buffering, the slurry is directly quenched with pure water and forcibly washed until neutral to obtain a neutral wet filter cake; in the third step, the strongly acidic composite acid leaching base solution of Example 1 is not used, but a weakly acidic base solution containing equal amounts of sodium lignosulfonate and tetrasodium ethylenediaminetetraacetate with an initial pH value fixed at 2.8 is directly prepared. After adding this neutral wet filter cake, acid or alkali is manually added dropwise throughout the reaction process to forcibly maintain the pH of the system at a constant 2.8 for the acid leaching reaction. All other steps are the same.

[0053] Comparative Example 4: Compared to Example 1, the difference lies in the preparation of the composite acid leaching base solution in the third step. Sodium lignosulfonate is not added during preparation; only 5 kg of tetrasodium ethylenediaminetetraacetate is added, and the missing mass is made up with hydrochloric acid solution to a total weight of 1000 kg. That is, this composite acid leaching base solution contains only EDTA-4Na and no sodium lignosulfonate. All other aspects are the same.

[0054] Comparative Example 5: Compared to Example 1, the difference lies in the preparation of the composite acid leaching base solution in the third step. In this step, ethylenediaminetetraacetic acid tetrasodium salt (EDTA-4Na) is not added; only 2 kg of sodium lignosulfonate is added, and the missing mass is made up with hydrochloric acid solution to a total weight of 1000 kg. That is, this composite acid leaching base solution contains only sodium lignosulfonate and no EDTA-4Na. All other aspects are the same.

[0055] Test Example 1-3: Test Example 1: Kinetic Verification of the Second-Step Buffer System Preset and the Third-Step Spontaneous pH Flow The specific experimental instructions are as follows: In the third step of Example 1, the alkaline wet filter cake containing ammonia and ammonium salt components was completely transferred to an acid-resistant reactor containing a composite acid leaching base solution. Mechanical stirring was started immediately, and an acid-resistant industrial online pH meter pre-installed on the side of the reactor baffle was turned on simultaneously for real-time monitoring.

[0056] The moment when the wet filter cake is fed and the stirrer reaches its rated speed is set as 0 minutes of reaction. The initial relatively stable pH value of the system is recorded as the baseline data for the start of migration.

[0057] Under operating conditions of 20-30℃ and constant mechanical stirring rate, the true pH value of the system was continuously read at a fixed recording period of 10 minutes, and the entire monitoring process lasted for 90 minutes. To reduce measurement noise caused by local concentration fluctuations in the slurry, the value of each recording node was taken as the arithmetic mean of the instrument readings within 15 seconds before and after that node.

[0058] When the reaction reaches 90 minutes, data acquisition is stopped, the continuous log of the monitoring device is exported, the data at the corresponding time points are extracted, and the kinetic data of the change of hydrogen ion concentration in the system with reaction time are obtained.

[0059] Table 1. Dynamic changes in pH value over time in the acid leaching reaction system of Example 1. in conclusion: According to Table 1 and Figure 1 Data, Figure 1 This is a graph showing the measured pH value of the acid leaching slurry as a function of reaction time in an embodiment of the present invention. Figure 1 The solid line in the middle represents the pH migration trend line fitted based on discrete sampling points. Figure 1 The scatter plots represent the measured pH values ​​at various time points, the smooth curve reflects the overall evolution trend of pH values, and the pH stability baseline indicates the weakly acidic range where the system eventually tends towards dynamic equilibrium. The data in the graphs map the mass transfer kinetics of residual buffering material in the filter cake diffusing into the liquid phase system and undergoing acid-base neutralization.

[0060] According to Table 1 and Figure 1 According to the data, the acid leaching system set in this process does not require external manual intervention. The residual components brought in by the filter cake from the previous process can achieve a spontaneous and smooth transition of the system's pH value. In the initial stage of the reaction (0 to 10 minutes), the system pH value is in the strongly acidic range of 0.50 to 0.92. At this time, the concentration of free hydrogen ions in the system is extremely high. This thermodynamic environment can rapidly penetrate the interlayer of microcrystalline graphite, attack and dissolve the encapsulated iron, aluminum, and other metal oxide impurities dissociated by the submolten salt, and convert them into free metal cations.

[0061] As the reaction time increased (20 to 60 minutes), the pH value of the system showed a non-linear upward trend. The ammonia and ammonium sulfate components trapped in the wet filter cake pores gradually diffused into the bulk solution under mechanical stirring. The ammonia molecules entering the liquid phase continuously consumed free hydrogen ions in the system, and the generated ammonium ions, together with the original ammonium ions, constructed a buffer system with anti-interference capabilities. The pH migration rate at this stage was controlled by the mass transfer and diffusion resistance at the solid-liquid interface within the filter cake pores, exhibiting a gradual increase and providing a sufficient window for the strong acid to dissociate metallic impurities.

[0062] In the later stages of the reaction (70 to 90 minutes), the pH value of the system stabilized within a slight fluctuation range of 2.71 to 2.81, achieving a dynamic equilibrium between the buffer system composed of ammonia and ammonium salts and the residual acid in the composite acid leaching base solution. The reaction solution remained in a weakly acidic environment at around 2.8, avoiding the sensitive range where silicic acid undergoes violent condensation under extremely acidic conditions. Combined with the steric hindrance effect of sodium lignosulfonate, the stability of soluble monomeric silicic acid was maintained, preventing the precipitation of silicic acid colloids and clogging of the filter press. Simultaneously, this pH environment fell within the thermodynamic window where tetrasodium ethylenediaminetetraacetate maximizes the complexation constant of transition metal ions such as iron and aluminum, allowing the metal ions dissociated in the early stages to be targeted, chelated, and masked, preventing secondary hydrolysis and precipitation reactions during the washing stage and ensuring the purity of the final microcrystalline graphite product.

[0063] Test Example 2: Dynamic monitoring of soluble silica concentration within the pH range in the third step The specific experimental instructions are as follows: During the third step of the reaction in Example 1, the pH changes within the system were monitored in real time using an online pH meter installed in the bypass of the reactor. Three sampling points were set: the initial strong acid stage, the wandering relay stage, and the final stable stage, with target pH values ​​of 0.5, 1.5, and 2.8, respectively.

[0064] When the measured values ​​of the online pH meter reach 0.52, 1.48 and 2.81 respectively, the sampling valve of the reactor is opened simultaneously, and 50 ml of suspension slurry is extracted from each of the stirred phases as the sample to be tested.

[0065] The extracted slurry sample was immediately placed in a centrifuge and centrifuged at 8000 rpm for 3 minutes. After separation, the supernatant was used as the test solution for the concentration of monomeric soluble silica.

[0066] The silicon content in the clear solution was determined using the silicomolybdate blue colorimetric method. An appropriate amount of the clear solution was transferred and diluted to a fixed volume, then a fixed volume of acidic ammonium molybdate solution was added. The solution was left at room temperature for a set time to allow the monomeric silicic acid and oligomeric silicic acid to react with the ammonium molybdate to form a yellow silicomolybdate heteropolyacid.

[0067] Subsequently, 1-amino-2-naphthol-4-sulfonic acid reducing agent was added to the reaction solution to reduce silicomolybdenum yellow to silicomolybdenum blue complex. The absorbance of the solution was measured at a wavelength of 815 nm using a UV-Vis spectrophotometer. Combined with a pre-calibrated silica standard curve, the true concentration of monomeric soluble silicic acid in the liquid phase system at each sampling point was calculated.

[0068] Table 2. Test data of monomeric silicic acid concentration at different pH points in the acid leaching system of Example 1 in conclusion: Table 2 records the actual concentration and relative retention rate of monomeric silicic acid in liquid phase samples taken at three representative pH points during the acid leaching reaction in the third step of Example 1. Figure 2 This is a bar chart showing the monomeric silicate concentration of the acid leaching slurry at different measured pH values ​​in the embodiments of the present invention. Figure 2 The horizontal axis corresponds to the measured pH value of the reaction system at different stages of evolution, and the vertical axis represents the concentration of monomeric silicic acid in the liquid phase. The concentration values ​​and the percentage retention rate relative to the initial strong acid stage are marked above the columns. The chart intuitively shows that during the entire process of the system's pH value transitioning to the traditional silicic acid polycondensation sensitive region, the monomeric silicic acid concentration only experiences a slight decrease, without a precipitous drop caused by large-scale dehydration polycondensation.

[0069] According to the data in Table 2, in Example 1, the concentration of monomeric silicic acid in the liquid phase remained highly stable during the pH evolution of the acid leaching reaction system from 0.50 to 2.81. At the strong acid starting point of pH 0.50, silicon was dissociated into the liquid phase, and the measured silicic acid concentration was 3.46 g / L. When the pH of the system shifted to the traditional silicic acid condensation sensitive zone of pH 2.81, the measured concentration of monomeric silicic acid remained at 3.21 g / L, with a relative retention rate of 92.8%. In conventional inorganic acid leaching purification processes, when the pH of the silicic acid-containing liquid phase system rises to the range of 2 to 3, the silanol groups between free silicic acid molecules near the isoelectric point undergo dehydration condensation reaction, generating a three-dimensional network silicic acid gel that precipitates out, resulting in a sharp drop in the concentration of monomeric silicon in the liquid phase.

[0070] The test results show that sodium lignosulfonate introduced into the composite acid leaching solution plays a role in steric hindrance and dispersion control within the system. The macromolecular backbone of sodium lignosulfonate and its negatively charged sulfonic acid groups adsorb and coat the monomeric silicic acid or primary oligomeric silicic acid molecules, forming a three-dimensional hydration protective layer with electrostatic repulsion, which physically blocks the collisional bonding pathways between silicic acid molecules. During the reaction window period when the pH of the system spontaneously rises to meet the thermodynamic conditions for targeted complexation and iron removal by tetrasodium ethylenediaminetetraacetate, this protective mechanism ensures that a large amount of dissociated free silicon remains in a monomeric soluble state. The soluble silicon is discharged from the system with the filtrate from the subsequent solid-liquid separation process, cutting off the physical source of blockage of the micropores of the filter cloth in the filter press equipment by silica gel backmixing, avoiding secondary encapsulation of residual iron, aluminum, and other metallic impurities in the interlayer by the condensation colloid, and ensuring the continuity of the purification process and the impurity removal depth of the final product.

[0071] Test Example 3: Comparison Test of Comprehensive Physicochemical Indicators and Energy Consumption The specific experimental instructions are as follows: Graphite final products were prepared according to the process steps described in Examples 1 to 5 and Comparative Examples 1 to 5, and relevant operating parameters during the production process were collected.

[0072] The fixed carbon content and ash content of the final graphite products in each group were determined according to the national standard GB / T 3521-2008 "Methods for Chemical Analysis of Graphite". The sampling amount, calcination temperature and weighing procedure were performed in accordance with the standard, and the calculation results are expressed as mass percentage.

[0073] The iron impurity content in the final graphite products of each group was determined using inductively coupled plasma optical emission spectrometer (ICP-OES). Graphite samples were microwave digested, diluted to a fixed volume, and then tested using the instrument. Results are expressed in parts per million (ppm).

[0074] Record the solid-liquid separation time of the slurry in a standard plate and frame filter press after the third step of acid leaching reaction for each group. A uniform operating filtration pressure of 0.6 MPa was set, and the time required for a unit volume of slurry to complete filter cake dewatering was calculated. The average filtration time was then expressed in minutes per cubic meter (min / m³). 3 )express.

[0075] The electrical energy consumed by the equipment in the first step of the dissociation reaction in each group was statistically analyzed. Using the total power consumption per ton of ore in the first step of the traditional high-temperature roasting process in Comparative Example 1 as a benchmark reference value (denoted as 100%), the actual power consumption in the first step reaction of each embodiment and comparative example was read by an industrial electricity meter installed at the heating equipment end, and the relative energy consumption percentage was calculated.

[0076] Table 3. Comparison of comprehensive physicochemical indicators and energy consumption of each embodiment and comparative example. in conclusion: Table 3 records the comprehensive physicochemical test and statistical data of Examples 1 to 5 and Comparative Examples 1 to 5 in terms of final product purity (fixed carbon, iron content, ash content) and process operation indicators (pressure filtration time, relative energy consumption). Figure 3 This is a bar chart comparing the iron content and average filtration time of the final products of the embodiments of the present invention and each comparative example. Sub-chart (a) compares the iron content, and sub-chart (b) compares the average filtration time. This chart visually reflects the specific negative impacts of removing one or more core process features (such as removing pH migration in Comparative Example 3, removing sodium lignosulfonate in Comparative Example 4, and removing EDTA in Comparative Example 5) on the final iron removal effect and filtration / dehydration performance.

[0077] According to the data in Table 3, the final products of Examples 1 to 5 all achieved a fixed carbon content of over 99.7%, an iron impurity content controlled below 35 ppm, and an ash content below 0.2%. Furthermore, the average filtration time was short and the relative energy consumption was low, verifying the feasibility of this scheme. Compared to Comparative Example 1, the first step of the Example group reduced the relative energy consumption by approximately 60%, shortened the average filtration time by approximately 88%, and increased the fixed carbon content of the final product by approximately 3 percentage points. Comparative Example 1 employed a high-temperature calcination process, which resulted in high energy consumption and failed to resolve the physical encapsulation of graphite by impurities such as silicates, leading to obstructed subsequent acid leaching and filtration, and a low purification limit.

[0078] Comparing Example 1 and Comparative Example 2, the final product ash content of Comparative Example 2 was 1.68%, higher than that of Example 1 (0.11%). Comparative Example 2 used an equal mass of sodium hydroxide to prepare a single-alkali system. Under operating conditions of 250°C, the lack of a eutectic environment with potassium ion participation and the large-radius ion polarization penetration effect resulted in insufficient ability of the single-alkali system to dissociate the crystalline silicate ore. Undamaged silicate impurities remained in the carbon framework, leading to a higher final ash content.

[0079] Compared with Comparative Example 1, Comparative Example 3 had an iron content of 812 ppm (as shown in sub-figure (a)). Comparative Example 3 eliminated the pre-set buffer system step and carried out leaching in a weakly acidic environment with a constant pH of 2.8. The dynamic process of spontaneous migration from strong acid to weak acid was lost, and the system could not initially provide a high concentration of free hydrogen ions to dissociate the encapsulated iron oxides. This resulted in the iron impurities encapsulated between the graphite layers failing to be converted into a free state for removal, verifying the role of the dynamic mechanism of first strong acid dissociation followed by weak acid complexation in the removal of metal impurities.

[0080] Compared with Comparative Example 4, the average pressure filtration time of Comparative Example 4 increased to 185.3 min / m.3 (As shown in sub-figure (b)), the iron content increased to 356 ppm, and the ash content reached 1.35%. In the acid leaching system of Comparative Example 4, sodium lignosulfonate was removed. When the pH value of the reaction system was at 2.8, a sensitive range for silica condensation, the free silica in the liquid phase lost the steric hindrance and electrostatic repulsion protection provided by the macromolecules, and underwent a dehydration condensation reaction to generate a three-dimensional network of silica gel. The silica gel blocked the micropores of the filter cloth of the filter press, which hindered the filtration operation. It also physically sealed the free iron ions that had previously dissociated into the liquid phase, blocking the complexation masking channel of EDTA-4Na, resulting in a decrease in the overall iron removal rate.

[0081] Compared with Comparative Example 5, the iron impurity content of Comparative Example 5 reached 1745 ppm (as shown in sub-figure (a)). Comparative Example 5 removed EDTA-4Na in the acid leaching system. Although the filtration time was not affected, the pH of the system fluctuated and stabilized at a weakly acidic environment of 2.8 in the later stages of the reaction. The free metal cations such as iron and aluminum that were dissociated earlier lacked the targeting and masking effect of the coordinating chelating agent, resulting in hydrolysis. The generated metal hydroxide precipitate re-attached to the interlayer of the microcrystalline graphite sheets, leading to excessive metal impurities in the final product. This demonstrates the necessity for the dual auxiliary agents in the composite acid leaching base solution to work synergistically under specific pH conditions.

Claims

1. A composite purification process for the large-scale preparation of high-purity microcrystalline graphite with low energy consumption, characterized in that, Includes the following steps: Microcrystalline graphite ore powder was mixed with a eutectic submolten salt system containing sodium hydroxide, potassium hydroxide and deionized water, and a dissociation reaction was carried out under pressure and heating conditions to obtain the reaction system. The reaction system is cooled and depressurized, and an ammonium sulfate aqueous solution is added to react and obtain an alkaline precipitate slurry. The amount of ammonium sulfate aqueous solution added is controlled until the final pH value of the alkaline precipitate slurry reaches 11.6-12.

0. Then, the alkaline precipitate slurry is subjected to solid-liquid separation to obtain a wet filter cake containing some residual ammonia and slightly alkaline mother liquor. The alkaline wet filter cake containing the ammonia and ammonium salt buffer system is added to a composite acid leaching base solution containing hydrochloric acid base solution, sodium lignosulfonate and tetrasodium ethylenediaminetetraacetate for acid leaching reaction to obtain acid leaching slurry. Under mechanical stirring, the residual alkali components carried in the pores of the wet filter cake neutralize part of the free acid in the acid leaching slurry. By controlling the solid-liquid ratio of the wet filter cake and the composite acid leaching base solution, the pH value of the acid leaching slurry is gradually increased and finally placed in the slightly acidic range of 2.71-2.81 to obtain the acid-leached slurry. The acid-leached slurry is subjected to solid-liquid separation to obtain the final filter cake. The final filter cake is then washed and dried to obtain a high-purity microcrystalline graphite product.

2. The composite purification process for low-energy, high-purity microcrystalline graphite preparation in large quantities according to claim 1, characterized in that, The eutectic submolten salt system is made from the following raw materials in parts by weight: The sodium hydroxide is 40-58 parts, the potassium hydroxide is 42-60 parts, and the deionized water is 15-21 parts.

3. The composite purification process for low-energy, high-purity microcrystalline graphite preparation in large quantities according to claim 2, characterized in that, The preparation method of the eutectic submolten salt system includes: The sodium hydroxide and potassium hydroxide are mixed evenly to obtain a dry mixed alkali. Deionized water is slowly added to the dry mixed alkali, and the mixture is heated to 90-120°C using the heat of hydration. The mixture is then stirred in a sealed container until it reaches a completely melted, homogeneous liquid state, thus obtaining the eutectic submolten salt system.

4. The composite purification process for low-energy, high-purity microcrystalline graphite preparation in large quantities according to claim 1, characterized in that, The composite acid leaching base solution is made from the following raw materials in parts by weight: The solution contains 990-996 parts of hydrochloric acid solution with an initial pH of 0.3-0.7, 1-3 parts of sodium lignosulfonate, and 3-7 parts of tetrasodium ethylenediaminetetraacetate.

5. The composite purification process for low-energy, high-purity microcrystalline graphite preparation in large quantities according to claim 4, characterized in that, The preparation method of the composite acid leaching base solution includes: Sodium lignosulfonate and sodium ethylenediaminetetraacetate are slowly added sequentially to the hydrochloric acid base solution. The mixture is continuously mechanically stirred at 20-30°C to convert the sodium ethylenediaminetetraacetate into free ethylenediaminetetraacetic acid particles under strong acid conditions and disperse them uniformly, thereby obtaining the composite acid leaching base solution, which is a uniformly dispersed suspension.

6. The composite purification process for low-energy, high-purity microcrystalline graphite preparation in large quantities according to claim 1, characterized in that, The mass ratio of the microcrystalline graphite ore powder to the eutectic submolten salt system is 100:(115-121).

7. The composite purification process for low-energy, high-purity microcrystalline graphite preparation in large quantities according to claim 6, characterized in that, The target temperature for the dissociation reaction is 220-280℃, the pressure is controlled to be stable at 1.5-3.5MPa, and the reaction time is 1.5-2.5 hours.

8. The composite purification process for low-energy, high-purity microcrystalline graphite preparation in large quantities according to claim 1, characterized in that, Cooling and depressurizing the reaction system means cooling the reaction system to 50°C and depressurizing it to atmospheric pressure. The mass fraction of the ammonium sulfate aqueous solution added to the reaction system is 15.0%.

9. The composite purification process for low-energy, high-purity microcrystalline graphite preparation in large quantities according to claim 1, characterized in that, During the acid leaching reaction, the pH value of the acid leaching slurry spontaneously and slowly increases from the initial 0.3-0.7; The entire acid leaching reaction process was carried out at 20-30°C for 1.5 hours.

10. The composite purification process for low-energy, high-purity microcrystalline graphite preparation in large quantities according to claim 1, characterized in that, When performing solid-liquid separation on the acid-leached slurry, a filter press is used for filter press separation, and the operating pressure is 0.6 MPa; The washing of the final filter cake refers to washing the final filter cake with deionized water until the washing filtrate is neutral.